Efficiency of black mustard Brassica nigra L. in remidiating soils contaminated with lead and cadmium. - زياده ميسون; محمّد دكّه; فينّا حمّود (Latakia University Journal -Biological Sciences Series, 2024)
This study dealt with evaluating the ability of the black mustard plant Brassica nigra L. to accumulate cadmium and lead, to determine its efficiency for use in phytoremediation of soil contaminated with lead and cadmium, based on pot-experiment, which soil was treated with cadmium nitrate and lead nitrate at concentrations of 3-15-30 mg cadmium/kg soil and 100-300-700. mg lead/kg soil. The results of the study showed that there was a significant effect of the concentration of lead and cadmium in the soil on the decrease in the wet and dry weight of the roots and the shoots in all treatments compared to the control, while the germination rate of black mustard seeds was not significantly affected. There was also a significant effect of the concentration of lead and cadmium in Soil content of roots and shoots of black mustard plants of both minerals. The black mustard plant can be considered a potential candidate for use in phytoremediation of cadmium by means of phytoextraction in sites with low pollution, because it has BAC and TF˃1 values, and it did not behave as a hyper-accumulating plant under the conditions of the current research and the characteristics of the soil used in it. The black mustard plant did not show efficiency in extracting lead, as all parameters were less than one.